Foundations of athletic training prevention, assessment, and management - Anderson, Marcia K.; Barnum, Mary (2021)
"Four major goals were established for this the seventh edition of the Foundations of Athletic Training. The primary goal was to support the transition of the athletic training education program from the undergraduate to the graduate level degree by including content identified in Section IV (Curricular Content) of the CAATE® 2020 Standards for Accreditation of Professional Athletic Training Program. Specific content relating to core competencies, patient/client care, prevention, health promotion, and wellness and health care administration are introduced early and imbedded throughout the text. A second goal was to continue to provide the most current and comprehensive evidence-based content related to the prevention, assessment, and management of injuries and illnesses sustained by physically active individuals. We have adopted a writing style that promotes clinical reasoning, seeks to demonstrate the value of utilizing differential diagnosis strategies, and moves the learner toward adopting reflective practice skills. In an effort to continue our tradition of providing special pedagogical features in a visually pleasing format, multicolor borders and formatting have been used to identify critical boxes, application strategies, and tables as a way to highlight key information"--Provided by publisher.
"Comprehensive and evidence-based, Foundations of Athletic Training, 7th Edition, integrates basic medical concepts and related scientific information to help readers develop a strong foundation in athletic training best practices. The text's practical, problem-solving approach to the prevention, recognition, assessment, management, and disposition of sports-related injuries and diseases helps students learn to think like practitioners. Fully aligned with the BOC competencies, the 7th Edition has been extensively updated, expanded, and reorganized to reflect the changing role of today's athletic trainer and includes a powerful suite of engaging learning tools to help students succeed.New chapters on Healthcare Administration, Leadership and Advocacy Professionalism, and Patient-Centered Care and extensively revised content throughout reflects the latest practices and helps you meet the challenges of today's healthcare environment.Application strategies offer step-by-step instructions on how to perform skills, conduct assessments, and teach injury prevention exercises.EMS alerts highlight emergency situations requiring immediate medical attention. Critical thinking scenarios and questions teach you to critically analyze information and apply decision-making knowledge and skills to problems presented.Full-color images and anatomical illustrations help you confidently locate key muscles, nerves, and blood vessels and recognize sports-related injuries and medical conditions.Application questions challenge you to apply what you've learned.eBook available for purchase. Fast, smart, and convenient, today's eBooks can transform learning. These interactive, fully searchable tools offer 24/7 access on multiple devices, the ability to highlight and share notes, and more"--Provided by publisher.
Athletic training is healthcare -- Prevention, health promotion, and wellness -- Foundations of clinical assessment and diagnosis -- Foundations of therapeutic intervention -- Assessment and diagnosis of musculoskeletal conditions -- Assessment and diagnosis of general medical conditions.
MS Salazar (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Sports injuries; Sports injuries -- Treatment; Athletes -- Health and hygiene; MEDICAL / Sports Medicine